EKSISTENSI PERPUSTAKAAN PERGURUAN TINGGI DI MASA PANDEMI COVID-19 - Barokah, Lailatul (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2021)
This study aims to determine the existence of university libraries during the COVID-19 pandemic. This type of research is a literature study. Where in collecting data using various references that are relevant to the observed phenomena such as from books, journals, news, documents, historical stories, and others. Observations were not carried out because large-scale social restrictions were still in effect. The results of the study show that any type of library until now still closes its doors to provide services, both borrowing and returning book collections. Especially in the school library where if the school closes, the library will follow suit. Especially in the university library as a support for achieving university goals related to the implementation of the Tri Dharma of Higher Education including education, research, and community service. During the Covid-19 pandemic, the librarian's creative and innovative ideas played a very important role in keeping the library alive in improving human resources.